Caribbean labour relations systems : an overview - Goolsarran, Samuel J. (ILO Port of SpainTT, 2002)
Provides the historical background which helped to shape the system of industrial relations. Presents an overview of legal frameworks and looks at the influence of the International Labour Organization and International Labour Standards. Highlights developments and trends in social dialogue and social partnership. Presents a summary of the main body of labour legislation in each of the twenty-one (21) countries and territories of the English and Dutch-speaking Caribbean.